Project on Human Development in Chicago Neighborhoods (PHDCN): Wide Range Achievement Test, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. The Wide Range Achievement Test was designed to measure reading recognition and spelling.